(untitled) (World Bulletin of Public Health, 2022)
Over the past few years, oral mucosa emerged as a reliable and popular donor tissue for urethral substitution. Our study is a prospective study to evaluate the outcome of the use of oral mucosa graft in urethroplasty, reporting its effectiveness and morbidity on the donor site. From January 2018 to January 2019, 20 patients with anterior urethral strictures and complex hypospadias repair had a urethroplasty using oral mucosa grafts. Patients’ age ranged between 7 to 63 years. Patients were divided into two groups. Group (A) which included eight patients managed by buccal muucosa graft, and group (B) which included 12 patients managed by lingual mucosa graft. All patients were followed up for three months duration. Symptoms related to the donor site were assessed within 48 hours of surgery, then at one week, one month, and three months after surgery. Oral mucosa graft urethroplasty appears to be a successful and technically feasible option for the management of patients with urethral stricture either as a single stage in urethral strictures or staged procedure in complex cases of stricture due to complex or failed hypospadias surgery. Oral pain is not different after both grafts. In the early postoperative period, differences in oral morbidity are present between BMG and LMG